Geliat Penulisan Kitab Hadis di Pesantren: Studi Kitab Fadlail Al-Tahajjud wa Qiyam Al-Lail Karya Ahmad Yasin bin Asmuni
It must be acknowledged that hadith study activities in Islamic boarding schools are still less popular when compared to other scientific studies such as Tafsir and Fiqh. Due to this lack of attention to hadith studies, the works of Indonesian scholars in the field of hadith, especially pesantren scholars, are very minimal. Moreover, contemporary scholars, such works are almost non- existent. This article discusses the book Fad